2011
DOI: 10.1111/j.1600-6143.2011.03640.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Traditional Risk Factors for Rejection and Graft Loss After Kidney Transplantation

Abstract: Single antigen bead (SAB) testing permits reassessment of immunologic risk for kidney transplantation. Traditionally, high panel reactive antibody (PRA), retransplant and deceased donor (DD) grafts have been associated with increased risk. We hypothesized that this risk was likely mediated by (unrecognized) donor-specific antibody (DSA). We grouped 587 kidney transplants using clinical history and SAB testing of day of transplant serum as 1) unsensitized; PRA=0 (n= 178), 2) 3rd party sensitized; no DSA (n=363)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
149
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 34 publications
19
149
3
3
Order By: Relevance
“…On the other hand, rejections might have been missed or not registered. Others have shown that in living donor transplants, DSAs was an important predictor of antibody‐mediated rejection, while this was not the case for graft failure 31. Using the limited rejection data that we had, we observed that patients with pretransplant DSAs had a higher incidence of rejection in living as well as deceased donor transplants (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, rejections might have been missed or not registered. Others have shown that in living donor transplants, DSAs was an important predictor of antibody‐mediated rejection, while this was not the case for graft failure 31. Using the limited rejection data that we had, we observed that patients with pretransplant DSAs had a higher incidence of rejection in living as well as deceased donor transplants (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…Studies from numerous investigators reported of AMR and/or graft loss in patients who's donor-specific antibody (DSA) were undetectable by complement dependent cytotoxicity assays but present by multiplex solid phase assays (36)(37)(38)(39)(40). Thus, the preferred donor lacks the HLA antigen(s) corresponding to antibodies identified by solid phase technology.…”
Section: Theory Versus Realitymentioning
confidence: 99%
“…The identification of risk factors for AR events may therefore contribute to optimization of therapy. Previous studies have identified histocompatibility measures and certain donor information to be amongst such factors [15,16]. However, owing to differences in the studied populations, observation periods, treatment protocols and methods of analysis, the significance of such factors may not be generalizable to other study populations, making it necessary to investigate to what extent previous findings can be confirmed in the new population.…”
Section: Introductionmentioning
confidence: 99%